Corporate Governance on Natural Resources: Lessons from the Past Years Scandal, Fraud, and Corruption - Naomi, Prima; Akbar, Iqbal (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
The recognition of corporate governance as one of the solutions to scandal, fraud, and corruption has generated interest among scholars who seek to comprehend the underlying theoretical mechanism of corporate governance practices. Using scientific literature from the Web of Science and news media, this research attempts to probe the conceptual basis for corporate governance in preventing crimes in managing natural resources. Based on the theories of corporate governance, this study reviews the framework and elaborates the challenges of implementing the practices of corporate governance in reducing scandal, fraud, and corruption. Agency and stakeholder theories are mostly used to scrutinize the practice of doing good business. We also evaluate how news media serve as an effective avenue for the public to receive unbiased information. Some major corporate cases reported in news media have indeed provoked scholars to shed light on the role of corporate governance in the presence of the crisis.